Implementasi Learning Management System sebagai Solusi Pembelajaran Materi Kepalangmerahan Menggunakan Metode KMSLC - Dafa Arta Anggara; Rahmat Aji Prasetyo; Ghois Abdullah Akmal; Ito Setiawan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This study aims to develop a Learning Management System (LMS) for kepalangmerahan management education in the Indonesian Red Cross Youth at SMK Wiworotomo Purwokerto The methodology employed is the Knowledge Management System Life Cycle (KMSLC) with the Meyer and Zack cycle approach, along with the spiral knowledge model by Nonaka and Takeuchi. Network infrastructure involves the internet, wireless access points, and private internet networks. Hardware and software include android devices with browser applications. Resource and data identification is carried out through discussions, interviews, and data entry, utilizing sources from PMR trainers, the Indonesian Red Cross website, and scholarly literature. The Knowledge Management (KM) team consists of PMR trainers, LMS developers, administrators, and PMR members. The system is implemented using WordPress and the TutorLMS plugin, with verification and validation testing conducted through black box testing. The research results demonstrate the successful development of the kepalangmerahan management education LMS in PMR SMK Wiworotomo Purwokerto, with a specific focus on disaster management education materials. This study contributes to improving effective learning access within PMR.